2007 10th IFIP/IEEE International Symposium on Integrated Network Management 2007
DOI: 10.1109/inm.2007.374825
|View full text |Cite
|
Sign up to set email alerts
|

Finding Elephant flows for optical networks

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 6 publications
0
23
0
Order By: Relevance
“…Although a considerable amount of flow characteristics were observed and correlated, the authors did not use various definitions for an IP flow, considering only the traditional 5-tuple flow definition 2 . In a previous work of ours [22], we concluded that there is no substantial variation in the definition of a flow in most of the investigated related works. As a result of that, we decided to perform our analysis by considering various definitions for a flow [22].…”
Section: Related Workmentioning
confidence: 61%
See 1 more Smart Citation
“…Although a considerable amount of flow characteristics were observed and correlated, the authors did not use various definitions for an IP flow, considering only the traditional 5-tuple flow definition 2 . In a previous work of ours [22], we concluded that there is no substantial variation in the definition of a flow in most of the investigated related works. As a result of that, we decided to perform our analysis by considering various definitions for a flow [22].…”
Section: Related Workmentioning
confidence: 61%
“…In a previous work of ours [22], we concluded that there is no substantial variation in the definition of a flow in most of the investigated related works. As a result of that, we decided to perform our analysis by considering various definitions for a flow [22]. In that analysis we characterized IP flows eligible to the optical level only with respect to their size while observing the influence of using different definitions for a flow.…”
Section: Related Workmentioning
confidence: 61%
“…There are many definitions of flow available in the literature [16,17] but we follow the IP Flow Information Export (IPFIX) working group of the IETF [18]. As per IPFIX, a flow can be defined as a set of IP packets passing through a monitoring point in a network during a particular time interval.…”
Section: Preliminaries Of Information Theorymentioning
confidence: 99%
“…For example, a DNS request is usually sent using only one packet, so the resulting flow record can be exported almost immediately. However, some applications, e.g., video streaming, generate large number of packets over a period of time [13], therefore the inactive timeout should be longer. By analyzing the behavior of major application protocols we can make the flow cache management more effective.…”
Section: What Are the Impacts Of Application Protocol Measurement On mentioning
confidence: 99%